2020
DOI: 10.1155/2020/8574702
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Network Pharmacology‐Based Mechanism for Attenuation of Atherosclerosis in Apolipoprotein E Knockout Mice by Panax notoginseng Saponins

Abstract: This study investigated whether Panax notoginseng saponins (PNS) reduced atherosclerotic lesion formation in apolipoprotein E knockout (ApoE-KO) mice and illustrated the potential mechanism for a network pharmacology approach. Pharmacodynamics studies on ApoE-KO mice with atherosclerosis (AS) showed that PNS generated an obvious anti-AS action. Then, we explored the possible mechanisms underlying its anti-AS effect using the network pharmacology approach. The main chemical components and their targets of PNS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The activation of the NF-κB signaling pathway influences a broad range of biological processes [47]. The interaction of RAGE and its ligand AGE is associated with oxidative stress and inflammatory responses [48]. MAPK signaling pathway regulates many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the NF-κB signaling pathway influences a broad range of biological processes [47]. The interaction of RAGE and its ligand AGE is associated with oxidative stress and inflammatory responses [48]. MAPK signaling pathway regulates many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Notoginsenoside R1 exerts cardioprotective effects against diabetic cardiomyopathy through its inhibition of oxidative stress and apoptosis [ 27 , 28 ]. Pharmacodynamics studies showed that Panax notoginseng saponins (PNS) generated an obvious antiatherosclerosis action [ 29 ]. The application of core herbal prescription has confirmed that “Tonifying Qi, Nourishing Yin, Activating Blood, and Eliminating Phlegm” are the most commonly used therapeutic methods for patients with CHD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high‐density lipoprotein cholesterol (HDL‐C) is regarded as an anti‐atherosclerotic factor due to its key role in reverse cholesterol transport (RCT) from foam cells to the liver, coupled with its anti‐inflammatory and anti‐apoptotic properties (Rye & Barter, 2014). Numerous saponins or saponin‐rich extracts, such as Panax notoginseng (PNS), soybean saponins (SS), jujuboside A, and steroidal saponins in garlic, have demonstrated their effects on serum lipids in experimental studies (Hu et al, 2022; Long et al, 2020; Miao et al, 2020; Xie et al, 2020). It is important to note that a growing body of research has revealed the ability of various saponins to regulate lipid synthesis and reverse transport, thus impeding the progression of hyperlipidemia and atherosclerosis.…”
Section: Mechanism Of Saponins In the Treatment Of Atherosclerosismentioning
confidence: 99%